Deconstructing History of the Lie According to Jacques Derrida (Raparin Journal of Humanities (RJH), 2023)
Lying, which is the product of reason, is an ancient human phenomenon and one of man's evils. The act of lying is the act of saying. This saying is a vague concept in the history of philosophy and contains various questions. Philosophical questions about lying include other concepts (eg, error, non-lying, truth, non-truth, veracity, deception, mislead, etc.). Since telling the truth is under threat in the new society and the increase in lying has affected the truth, this has made the truth itself questionable. Therefore, the narrative of lying history cannot be neutral unless all anti-lie concepts are explained in it. In this study, the focus will be on the deconstructing the history of lying, which is itself full of lies. This makes writing a lie history difficult.Hence we come to say that when Jacques Derrida (1930-2004)  in his book  established a genealogy of History of the Lie deconstructing the concept of lying and rewriting its history becomes a basis for understanding: lie and error, of lie and justification, of  lies and bad Intention, of of truth and good intention,  of lie and intention, of lie and interest.Therefore, we treat the book " History of the Lie" as a book of deconstructing writing about the meaning of lying. Thus, this research relates to Derrida's deconstructive way of analyzing the history of the lie. This way of research will appear when we work on the concept of lie and its similar concepts and we automatically plunge into the history of lie and dismantling that history. Because many factors in this history have influenced the production of lie, this causes the history of lie to change according to cultures and civilizations, and each culture and civilization has its own history of lie.